Kinerja Badan Pelayanan Perijinan Terpadu Satu Pintu (BPPTSP) dan Penanaman Modal Kota Denpasar Tentang Pelayanan Izin Mendirikan Bangunan di Kota Denpasar - Kresna Gerih, I Gst.Ag.Gd.Ag.; Yudartha, I Putu Dharmanu; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2019)
ABSTRACT The Denpasar City Government in this case to protect and manage these facilities has compiled Regional Regulations (Perda). The Denpasar City Regulation includes: Denpasar City Regulation Number 27 of 2011 concerning Regional Spatial Planning (RTRW) and Denpasar City Regulation Number 6 of 2001 concerning Building Permits. However, in its implementation there are still many people who have not yet realized the importance of having a Building Construction Permit. Hence, this study aims to find out how the performance of the One Stop Integrated Licensing Service Agency (BPPTSP) and Denpasar Capital Investment concerning Building Permit Services using the method descriptive qualitative research with data collection techniques in the form of observation, interviews, documentation and method of literature. Measuring the performance of public bureaucracy using performance indicators according to Dwiyanto (1995), namely productivity, service quality, responsiveness, responsibility, accountability. Keyword:Performance, Service, Izin Mendirikan Bangunan